Pengaruh motivasi kerja, lingkungan kerja, dan kepemimpinan kepala sekolah terhadap kinerja guru SD di Kecamatan Gunungwungkal Kabupaten Pati - Supri Yati (COLLASE (Creative of Learning Students Elementary Education), 2023)
The purposes of this research is to determine: 1) the influence of work motivation on teacher’s performance, 2) the influence of work environment on teacher’s performance, 3) the influence of principal leadership on teacher’s performance, 4) the influence of work motivation and work environment on teacher’s performance, 5) the influence of work motivation and principal leadership on teacher’s performance, 6) the influence of work environment and principal leadership on teacher’s performance, and 7) the influence of these three aspects; work motivation, work environment, and principal leadership on teacher’s performance. This type of research is quantitative research by using ex post facto approach. The population in this research is elementary school teachers in Gunungwungkal Subdistrict of Pati Regency with the total number of 183 people, and it is obtained 72 people as sample by using proportionated stratified random sampling technique. This research uses data analysis techniques using simple and multiple regression test. The results of study showed that work motivation has an effect on teacher’s performance of 35,2%. Work environment has an effect on teacher’s performance of 43,9%. Principal leadership has an effect on teacher’s performance of 40,1%. Work motivation and work environment have an effect on teacher’s performance of 54,0%. Work motivation and principal leadership have an effect on teacher’s performance of 46,5%. Work environment and principal leadership have an effect on teacher’s performance of 54,8%. Work motivation, work environment, and principal leadership have an effect on teacher’s performance of 58,0%.